Youth Cultures in the Age of Global Media - Buckingham, David; Bragg, Sara; Kehily, Mary Jane (Palgrave Macmillan, 2020)
This book explores the impact of globalisation and new technologies on youth cultures around the world, from the Birmingham School to the youthscapes of South Korea. In a timely reappraisal of youth cultures in contemporary times, this collection profiles the best of new research in youth studies written by leading scholars in the field...